Discourses of Diversity, Equality and Inclusion: Trenchant Formulations or Transient Fashions?. (23rd May 2012) - Oswick, Cliff; Noon, Mike
<x xml:space="preserve">Abstract</x> Using bibliometric analysis of published work, we examine the discursive trends, patterns and implications of three different anti‐discrimination solutions (equality, diversity and inclusion) over a 40‐year period from 1970 to 2010. The findings reveal that the anti‐discrimination discourses are consistent with management fashions, in terms of both their trends and the rhetorical strategies used by proponents to establish the dominance of their favoured approach, particularly by denigrating previous approaches. Practitioner‐facing academics play a key role in the process by giving shape, exposure and credibility to the anti‐discrimination solutions, but not in creating them. Only by breaking free of the oppositional discursive patterns can the debate move on to anti‐discrimination solutions that attempt to blend together equality, diversity and inclusion.